Neutrophil gelatinase-associated lipocal in protein levels as an acute appendicitis biomarker in children - Bakal, Unal; Sarac, Mehmet; Ciftci, Harun; Tartar, Tugay; Kocdemir, Esra; Aydin, Suleyman; Kazez, Ahmet (Springer International Publishing Ag, 2016)
Objective: Appendicitis is very commonly encountered in emergency clinics. There is an urgent need for early and accurate predictive biomarkers of appendicitis in order to save lives, because currently-available biomarkers are imprecise and their delayed response impairs the ability of emergency doctors and pediatric surgeons to provide timely and potentially effective therapies. This study was performed to determine whether changes in the blood levels of neutrophil gelatinase-associated lipocalin (NGAL) can help to diagnose acute appendicitis in children and distinguish acute appendicitis from abdominal pain. Methods: Sixty children were enrolled and divided into three groups, with 20 patients per group: Group 1 (patients with appendicitis), Group 2 (patients with abdominal pain) and Group 3 (control). Blood NGAL levels were determined by ELISA. Results: The basal average serum NGAL levels were 8.2 ng/ml for Group 1, 3.9 ng/ml for Group 2, and 3.3 ng/ml for Group 3. Twenty-four and 72 h after surgery the levels were 5.1 and 2.8 ng/ml, respectively, in Group 1, 2.9 and 2.8 ng/ml in Group 2, and 2.6, 2.7 ng/ml in Group 3. Setting the cut-off point to 7 generated an area under the receiving operating curve (ROC) curve at 95 % confidence interval with 77.3 % sensitivity and 97.4 % specificity. Conclusion: These data indicate a significant difference in NGAL values between basal and postoperative measurements in appendicitis patients (p < 0.05). The ROC curve results showed that NGAL is a promising novel biomarker for the differential diagnosis of acute appendicitis from abdominal pain.
Keywords: Lipocalin; Acute appendicitis; Biomarker; Pediatric surgeon